Evaluation of elastomeric dampers on the dynamic characteristics for vibration control in rotating machines - Darvind Asokan (2023)
Rotating machines experience high vibration levels due to various causes during operation. One of the commonly used method to reduce vibration in these machines is by incorporating squeeze-film dampers in the bearing assembly. These dampers are, however, complex in design and requires frequent maintenance of its oil supply mechanism. An alternative to the squeeze-film dampers are the elastomeric dampers, which are less complicated in their design and are almost maintenance free. These dampers are essentially vibration isolators as they also provide stiffness, in addition to damping, to the rotor-bearing system. Since there are no available analytical expressions to theoretically determine the dynamic characteristics of elastomeric dampers, these characteristics are commonly obtained from experiments. In most cases, however, the dynamic characteristics of these dampers are determined under stationary unilateral load, although they are subjected to rotating load during operation of the rotating machines. It is therefore hypothesised that the dynamic characteristics of these dampers under rotational load may differ from their dynamic characteristics under stationary unilateral load. The works presented in this thesis are aimed to address the limited work done in the past by determining and comparing the dynamic characteristics of the elastomeric dampers under unilateral stationary and rotational loads in addition to evaluating the effect of these speed dependent properties on the vibration response of a rigid rotor. The dynamic characteristics of the elastomeric dampers were evaluated using the frequency response function-based identification method. The frequency response functions were obtained from impact excitation tests undertaken on a rigid rotor test rig incorporating the elastomeric dampers. This set-up allowed the frequency response functions to be determined for both cases of stationary and rotating loads. A mathematical model of the rigid rotor test rig was formulated, and the frequency-dependent dynamic stiffness and damping coefficient / loss factor of the dampers were identified using this model and the measured frequency response functions. Polynomial curve-fitting functions were used to represent the frequency-dependent dynamic stiffness and damping coefficient / loss factor of the dampers. These functions were then used to theoretically determine the vibration response of a rigid rotor mounted on elastomeric dampers. The outcome from this work showed that the dynamic stiffness and damping coefficient / loss factor of the elastomeric dampers obtained under rotating load conditions may vary significantly, depending on frequency, from those obtained under stationary load condition. For both dynamic stiffness and damping coefficient, this variation was generally more pronounced for the range of frequencies in the vicinity of the resonant frequency. In this range, the maximum percentage error for both these characteristics, determined from the rotating rotor and stationary rotor was between 44.7% to 98.7%. However, for the loss factor, the variation was found to be more pronounced in the frequency range below the resonant frequency. The maximum percentage error difference here between the loss factor at stationary rotor with that of rotating rotor was between 21.7% and 96.3%, depending on the rotor speed in both cases of directions. The outcome of this work further revealed that the use of the dynamic characteristics of the elastomeric dampers obtained under stationary load condition to determine the vibration response of a rigid rotor subjected to rotating load may result in gross errors with a percentage between 78.1 – 95.6% in both the X- and Y- directions. The findings from this work indicated that the use of the dynamic characteristics of elastomeric dampers obtained under stationary load condition cannot accurately predict the vibration response of rotors subjected to rotating loads.